El litisconsorcio necesario: una institución equívoca en el derecho procesal administrativo.(The legal institution of the necessary joinder of defendants and its equivocal application in the administrative law) - Guzmán Cano, Julián Camilo; Mejía Álvarez, Carlos David (Revista CES Derecho, 2013)
El litisconsorcio necesario es una institución procesal cuya aplicación en materia contenciosaadministrativa ha sido equívoca. El Consejo de Estado en su jurisprudencia, la misma que guíalos pronunciamientos de los jueces y la conducta de la administración, ha confundido en diversasocasiones la finalidad de la institución apartándose de su desarrollo doctrinal y dejando enevidencia la falencia conceptual que se tiene sobre el litisconsorcio. Abstract The necessary joinder of defendants is a legal institution whose application in administrative lawhas been equivocal. The Council of State in its precedent, which guide the pronouncements ofjudges and the government, has repeatedly confused the purpose of the institution away from itsdoctrinal development and leaving in evidence the conceptual flaw that is on this topic.